Mechanical properties of CFG piles incorporating modified recycled aggregates by pre-soaking in alkaline slurry with industrial by-products - Shiping Zhang; Xiaoyu Huang; Junhui Zhang; Hiromasa Iwai; Lin Ma; Can Shi; Shicheng Li; Gaoqiao Wu (European Journal of Environmental and Civil Engineering, 2026)

The maize CMS-C fertility restore gene ZmRf4b encodes a SPL transcription factor that represses ZmMAP1D-mediated co-translational turnover of mitochondrial toxic ATP6C protein - Bing Li; Huaisheng Zhang; Runbo Zhang; Shicheng Feng; Fanli Yang; Congnian Ding; Xuyuan Shen; Keke Shao; Lu Yang; Yanan Lin; Dong Ding; Quancan Hou; et al. (Molecular Plant, 2026)

Land-use-driven terrestrial inputs and fresh-seawater mixing jointly shape sediment organic nitrogen in the Pearl River Estuary - Jia Yang; Pengju Li; Yunchao Wu; Jinlong Li; Feng Ye; Yuanbi Yi; Shicheng Lin; Ling Zhang; Zhijian Jiang; Songlin Liu; Xiaoping Huang; Ding He (Science China Earth Sciences, 2026)

Enhanced tolerance of triploid Betula pendula ‘Purple Rain’ to short-term chilling stress is associated with antioxidant capacity and BpSOD gene expression - Jie Zhang; Jingnan Li; Shicheng Li; Ling Lin; Long Liu; Xiaoyue Zhang; Ying Cui; Yujun Zhou; Jing Jiang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

A LINE-1 retrotransposon promotes SEMA3C expression as a cis-regulatory enhancer to sustain breast cancer stem cell survival - Qidong Xia; Jingwei Feng; Jiayao Pan; Wen Deng; Xiaoqi Weng; Jianhui Jiang; Lin Wang; Wenqian Xie; Yi Chen; Aiwei Bi; Jiang Li; Yiwen Lu; et al. (Science China Life Sciences, 2026)

Spatial patterns and environmental drivers of evapotranspiration across the Chinese Grassland Transect - Lexin Ma; Zhi Chen; Tianxiang Hao; Meng Yang; Quanhong Lin; Weikang Zhang; Lang Han; Zhaogang Liu; Mingyu Sun; Yong Lin; Xianjin Zhu; Shiping Chen; et al. (Journal of Hydrology, 2026)

Topic modeling help enhancing sustainable mobility - Xiao Li; Guangxi He; Peng Guo; Zhaohua Guo; Shicheng Lin; Shouji Du (Journal of Cleaner Production, 2025)

A neoflavonoid from the stems and leaves of Paris tengchongensis and its inhibitory activity against vascular calcification - Yan Chen; Shicheng Wu; Xuan Chen; Lin Zhang; Xirong Chen; Ya Zhu (Phytochemistry Letters, 2025)

Nano- and microplastics drive the dynamic equilibrium of amoeba-associated bacteria and antibiotic resistance genes - Min Zhou; Lu Ma; Zihe Wang; Shicheng Li; Yijun Cai; Meicheng Li; Lin Zhang; Cheng Wang; Bo Wu; Qingyun Yan; Zhili He; Longfei Shu (Journal of Hazardous Materials, 2024)

Insight into succinylated modified soy protein isolate-sodium alginate emulsion gels: Structural properties, interactions and quercetin release behavior - Sai Yang; Ziteng Lian; Lin Cheng; Xiuying Liu; Shicheng Dai; Xiaohong Tong; Huan Wang; Lianzhou Jiang (Food Hydrocolloids, 2024)

Investigation of Crack Propagation and Failure of Liquid-Filled Cylindrical Shells Damaged in High-Pressure Environments - Hongshuo Zhang; Dapeng Tan; Shicheng Xu; Tiancheng Hu; Huan Qi; Lin Li (Journal of Marine Science and Engineering, 2024)
Cylindrical shell structures have excellent structural properties and load-bearing capacities in fields such as aerospace, marine engineering, and nuclear power. However, under high-pressure conditions, cylindrical shells are prone to cracking due to impact, corrosion, and fatigue, leading to a reduction in structural strength or failure. This paper proposes a static modeling method for damaged liquid-filled cylindrical shells based on the extended finite element method (XFEM). It investigated the impact of different initial crack angles on the crack propagation path and failure process of liquid-filled cylindrical shells, overcoming the difficulties of accurately simulating stress concentration at crack tips and discontinuities in the propagation path encountered in traditional finite element methods. Additionally, based on fluid-structure interaction theory, a dynamic model for damaged liquid-filled cylindrical shells was established, analyzing the changes in pressure and flow state of the fluid during crack propagation. Experimental results showed that although the initial crack angle had a slight effect on the crack propagation path, the crack ultimately extended along both sides of the main axis of the cylindrical shell. When the initial crack angle was 0°, the crack propagation path was more likely to form a through-crack, with the highest penetration rate, whereas when the initial crack angle was 75°, the crack propagation speed was slower. After fluid entered the cylindrical shell, it spurted along the crack propagation path, forming a wave crest at the initial ejection position.

Effect of phlorotannins modification on the physicochemical, structural and functional properties of soybean protein isolate and controlled hydrolysates: Covalent and non-covalent interactions - Lin Cheng; Ziteng Lian; Xiuying Liu; Shicheng Dai; Lanxin Li; Mengmeng Wang; Ka Li; Kunyu Ren; Xiaohong Tong; Huan Wang; Lianzhou Jiang (Food Hydrocolloids, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Precipitation consistently promotes, but temperature oppositely drives carbon fluxes in temperate and alpine grasslands in China - Zhaogang Liu; Zhi Chen; Meng Yang; Tianxiang Hao; Guirui Yu; Xianjin Zhu; Weikang Zhang; Lexin Ma; Xiaojun Dou; Yong Lin; Wenxing Luo; Lang Han; et al. (Agricultural and Forest Meteorology, 2024)

Corrigendum to “Aroma characterisation of Liu-pao tea based on volatile fingerprint and aroma wheel using SBSE-GC-MS” [Food Chem. 414 (2023) 135739] - Wanjun Ma; Yin Zhu; Shicheng Ma; Jiang Shi; Han Yan; Zhi Lin; Haipeng Lv (Food Chemistry, 2023)

Effective CO2 capture by in-situ nitrogen-doped nanoporous carbon derived from waste antibiotic fermentation residues - Peiliang Liu; Shumeng Qin; Jieni Wang; Shuqin Zhang; Yijun Tian; Fangfang Zhang; Chenxiao Liu; Leichang Cao; Yanmei Zhou; Lin Wang; Zhangdong Wei; Shicheng Zhang (Environmental Pollution, 2023)

Aroma characterisation of Liu-pao tea based on volatile fingerprint and aroma wheel using SBSE-GC–MS - Wanjun Ma; Yin Zhu; Shicheng Ma; Jiang Shi; Han Yan; Zhi Lin; Haipeng Lv (Food Chemistry, 2023)

Morroniside inhibits Beclin1-dependent autophagic death and Bax-dependent apoptosis in cardiomyocytes through repressing BCL2 phosphorylation - Xueping Ke; Shicheng Yu; Shubiao Situ; Zhenqian Lin; Yiqiang Yuan (In Vitro Cellular & Developmental Biology - Animal, 2023)

Emulsifying properties and oil–water interface properties of succinylated soy protein isolate: Affected by conformational flexibility of the interfacial protein - Ziteng Lian; Sai Yang; Lin Cheng; Peilong Liao; Shicheng Dai; Xiaohong Tong; Tian Tian; Huan Wang; Lianzhou Jiang (Food Hydrocolloids, 2023)

Soy protein isolate-catechin non-covalent and covalent complexes: Focus on structure, aggregation, stability and in vitro digestion characteristics - Shicheng Dai; Peilong Liao; Yilun Wang; Tian Tian; Xiaohong Tong; Bo Lyu; Lin Cheng; Liming Miao; Weijie Qi; Lianzhou Jiang; Huan Wang (Food Hydrocolloids, 2023)

Variations of suspended sediment transport caused by changes in shoreline and bathymetry in the Zhujiang (Pearl) River Estuary in the wet season - Shicheng Lin; Jianwei Niu; Guangping Liu; Xing Wei; Shuqun Cai (Acta Oceanologica Sinica, 2022)